2018
DOI: 10.1016/j.vaccine.2018.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a stable CHO cell line for the expression of a MERS-coronavirus vaccine antigen

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) has infected at least 2040 patients and caused 712 deaths since its first appearance in 2012, yet neither pathogen-specific therapeutics nor approved vaccines are available. To address this need, we are developing a subunit recombinant protein vaccine comprising residues 377-588 of the MERS-CoV spike protein receptor-binding domain (RBD), which, when formulated with the AddaVax adjuvant, it induces a significant neutralizing antibody response and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 37 publications
0
65
1
1
Order By: Relevance
“…Using CHO cell technology, we have recently obtained the high-yield producer stable cell clones for production of glycan-masking Pan-H5 vaccines [29]. Similar strategies have been also reported for production of a homogeneous HIV-1 envelope SOSIP trimer vaccine [30] and a MERS-coronavirus vaccine antigen [31].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Using CHO cell technology, we have recently obtained the high-yield producer stable cell clones for production of glycan-masking Pan-H5 vaccines [29]. Similar strategies have been also reported for production of a homogeneous HIV-1 envelope SOSIP trimer vaccine [30] and a MERS-coronavirus vaccine antigen [31].…”
Section: Introductionmentioning
confidence: 82%
“…Cell clones that survived following treatment with 1 mM MTX were collected and analyzed by Western blotting using anti-rH7 antibodies (GeneTex Inc.) to confirm CHO-rH7 expression. The final selected rH7-expressing clones were cultured, and the culture supernatants were harvested for rH7 purification using nickel-chelated resin affinity chromatography (Tosoh), as previously described [29][30][31]. The purified rH7 proteins were treated with endoglycosidase H (Endo H) (New England BioLabs) or N-glycosidase F (PNGase F) (New England BioLabs) for Western blotting characterization.…”
Section: Expression and Purification Of Rh7 From Stable Clones Of Chomentioning
confidence: 99%
“…However, after comparing several versions of MERS-CoV RBD fragments with different lengths, it was found that a truncated RBD (residues 377-588) had the highest DPP4binding affinity and induced the highest-titer IgG antibodies and neutralizing antibodies against MERS-CoV, identifying its role as a critical neutralizing domain . Subsequently, several MERS-CoV subunit vaccines have been designed based on the identified critical neutralizing domain of RBD fragment, including those expressed in a stable CHO cell line (S377-588-Fc), fusing with a trimeric motif foldon (RBD-Fd), or containing single or multiple mutations in the RBD of representative human and camel strains from the 2012-2015 MERS outbreaks (Tai et al, 2016Nyon et al, 2018). These RBD proteins maintain good conformation, functionality, antigenicity, and immunogenicity, with ability to bind the DPP4 receptor and RBD-specific neutralizing mAbs and to elicit robust neutralizing antibodies cross-neutralizing multiple strains of MERS pseudoviruses and live MERS-CoV (Tai et al, 2016Nyon et al, 2018).…”
Section: Mers-cov Subunit Vaccines Based On Rbdmentioning
confidence: 99%
“…Use of an adjuvant, particularly MF59 or AddaVax, significantly improved both the humoral and T cell responses in subcutaneously immunized mice (Zhang et al, 2016b). Recently, a high-yield CHO cell line capable of large-scale production of this S1 RBD-Fc fusion product was described, strengthening the possibility of sustainable manufacture and human testing for this potential vaccine antigen (Nyon et al, 2018). Another recent study showed that 5 recombinant RBDs incorporating mutations which arose in different MERS-CoV outbreaks or in camel strains could induce neutralizing antibody responses against several MERS-CoV pseudoviruses (Tai et al, 2017).…”
Section: Current and Potential Treatmentsmentioning
confidence: 99%
“…In vivo (Mouse) Humoral response in mice; potential intranasal administration; improved by adjuvant; divergent strains/ escape mutants; CHO cell line (Du et al, 2013;Ma et al, 2014;Nyon et al, 2018;Tai et al, 2017;Zhang et al, 2015Zhang et al, , 2016b T cell and neutralizing antibody responses; entering human clinical trials; potential for veterinary use- (Langenmayer et al, 2018;Volz et al, 2015) ad5 or ad41 adenovirus expressing full-length S…”
Section: In Vitromentioning
confidence: 99%